Simultaneous measurement of antroduodenal motility, gastric emptying, and duodenogastric reflux in man. Issue 11 (November 1979) - Rees, W D; Go, V L; Malagelada, J R
Abstract : In six healthy individuals, the relationship between antroduodenal motor activity, duodenogastric reflux, and gastric emptying were simultaneously examined by combined use of multiple marker perfusion and miniature strain gauge transducers. An interdigestive pattern of motor activity was observed during the fasting period;duodenogastric reflux was of variable magnitude, but reproducible in each individual. Fasting reflux was significantly reduced during phase III of the interdigestive complex. Administration of 0.15 M sodium chloride into the stomach resulted in minor and inconsistent changes in antroduodenal motility, despite the rapid and similar pattern of gastric emptying in the six subjects. This study supports the concept that motor activity in the antroduodenal region does not affect gastric emptying of inert, isotonic fluids but may be involved in the regulation of duodenogastric reflux.